Case Study-Based Experiences and Advice on the Use of Autoethnographic Research Method in Organizational Research - Polichtchouk, Vasilisa; Varis, Keijo (American Journal of Management, 2025)
This article presents findings from a longitudinal autoethnographic case study (2016–2024) on the evolution of knowledge management within a large Finnish state-owned research and development institution. Offering a cultural perspective, the main researcher—an internal member of the organization— reflects on personal experiences while engaging in autoethnographic research. The article emphasizes lessons learned from conducting this type of research and proposes recommendations for producing high-quality autoethnographic work. It also briefly outlines the study’s theoretical framework, relevant literature, and key empirical insights. Through thematic narrative analysis, the study uncovered nine distinct patterns that shaped the organization’s knowledge management history. These patterns emerged through the fusion of empirical findings, theoretical knowledge, and intuitive application of a knowledge management framework. This framework evolved into a narrative model informed by four key perspectives: people, processes, technology, and the ‘I’ - the researcher's subjective lens.